Simultaneous Cranioplasty and External Ventricular Drain Implantation in Patients with Hydrocephalus: Case Series and Literature Review - de Macêdo, Lívio Pereira; Netto, Arlindo Ugulino; Franke, Kauê; Eugenio, Pierre Vansant Oliveira; Rocha, John Anderson da Silva; Júnior, Glaudir Donato Pinto; Medeiros, João Pedro Maia; Maricevich, Juan Pablo Borges Rodrigues; Almeida, Nivaldo S.; Azevedo-Filho, Hildo Rocha Cirne (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Introduction The increase in intracranial pressure (ICP) is a neurological complication resulting from numerous pathologies that affect the brain and its compartments. Therefore, decompressive craniectomy (DC) is an alternative adopted to reduce ICP in emergencies, especially in cases refractory to clinical therapies, in favor of patient survival. However, DC is associated with several complications, including hydrocephalus (HC). The present study presents the results of an unusual intervention to this complication: the implantation of an external ventricular drain (EVD) in the intraoperative period of cranioplasty (CP).Methods Patients of both genders who presented with HC and externalization of the brain through the cranial vault after decompressive hemicraniectomy and underwent EVD implantation, to allow the CP procedure, in the same surgical procedure, were included.Results Five patients underwent DC due to a refractory increase in ICP, due to automobile accidents, firearm projectiles, falls from stairs, and ischemic strokes. All evolved with HC. There was no uniform time interval between DC and CP. The cerebrospinal fluid (CSF) was drained according to the need for correction of cerebral herniation in each patient, before undergoing cranioplasty. All patients progressed well, without neurological deficits in the immediate postoperative period.Conclusion There are still several uncertainties about the management of HC resulting from DC. In this context, other CP strategies simultaneous to the drainage of CSF, not necessarily related to ventriculoperitoneal shunt (VPS), should be considered and evaluated more deeply, in view of the verification of efficacy in procedures of this scope, such as the EVD addressed in this study.
Keywords: cranioplasty; external ventricular drain; post-traumatic hydrocephalus; neurosurgery